2018
DOI: 10.1155/2018/4091497
|View full text |Cite
|
Sign up to set email alerts
|

Control of Blood Glucose for Type-1 Diabetes by Using Reinforcement Learning with Feedforward Algorithm

Abstract: Background Type-1 diabetes is a condition caused by the lack of insulin hormone, which leads to an excessive increase in blood glucose level. The glucose kinetics process is difficult to control due to its complex and nonlinear nature and with state variables that are difficult to measure. Methods This paper proposes a method for automatically calculating the basal and bolus insulin doses for patients with type-1 diabetes using reinforcement learning with feedforward controller. The algorithm is designed to ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…It is also common to find some reference values related to normal, hyper and hypoglycemia ranges in order to establish good rewards and penalties. However, we found that only five papers include the actions taken in the reward function [31,32,38,42,44]. We think it could be interesting to also consider the insulin doses in the reward function, which for example can lead to take less aggressive actions for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also common to find some reference values related to normal, hyper and hypoglycemia ranges in order to establish good rewards and penalties. However, we found that only five papers include the actions taken in the reward function [31,32,38,42,44]. We think it could be interesting to also consider the insulin doses in the reward function, which for example can lead to take less aggressive actions for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed algorithm provides more precise insulin dosage recommendation considering the patient’s current HbA 1c , BMI, activity level, or alcohol usage. Vrabie et al (2018) and 2 studies by Ngo et al (2018) applied a model-based RL algorithm for controlling blood glucose for type 1 Diabetes [22-24]. We used a data-driven approach and considered the blood glucose level feedback from the patient body for training the Q-learning algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, at each time step t , the algorithm selects a random action with a fixed probability, ε, based on the following formulation. Figure 5 shows the random action selection function, where 0≤ u t ≤1 is a uniform random number drawn at each time step t [23,24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant desirable states are obtained with the communication between a decision making agent and its environment during PID learning process 32 . Some of the significant elements included in the type‐1 diabetes detection of the proposed framework includes: as indicated in Equation (1), the patient states are included at the time instance k of state vector. Xk=gkgdkXkT …”
Section: Proposed Approachmentioning
confidence: 99%